Milton among Spaniards - Duran, Angelica (Early modern exchange., 2020)
Firmly grounded in literary studies but drawing on religious studies, translation studies, drama, and visual art, Milton among Spaniards is the first book-length exploration of the afterlife of John Milton in Spanish culture, illuminating underexamined Anglo-Hispanic cultural relations. This study calls attention to a series of powerful engagements by Spaniards with Milton's works and legend, following a general chronology from the eighteenth to the early twenty-first century, tracing the overall story of Milton's presence from indices of prohibited works during the Inquisition, through the many Spanish translations of Paradise Lost, to the author's depiction on stage in the nineteenth-century play Milton, and finally to the representation of Paradise Lost by Spanish visual artists.